GERALDINE CHAPLIN the gift of film performance. - RYBIN, STEVEN (International film stars., 2020)
This book analyses the distinctive screen art of Geraldine Chaplin and uncover parallels between her performances and her father's work on film and thereby explores the rich and surprising relationships between art cinema and silent film comedy, and between modernist and classical cinematic performance.